Muscle Cells - Recent Advances and Future Perspectives 2020
DOI: 10.5772/intechopen.85177
|View full text |Cite
|
Sign up to set email alerts
|

Orexin System and Avian Muscle Mitochondria

Abstract: In mammals, orexin A and B (also known as hypocretin 1 and 2) are two orexigenic peptides produced primarily by the lateral hypothalamus that signal through two G-protein-coupled receptors, orexin receptors 1/2, and have been implicated in the regulation of several physiological processes. However, the physiological roles of orexin are not well defined in avian (non-mammalian vertebrate) species. Recently, we made a breakthrough by identifying that orexin and its related receptors 1/2 (ORXR1/2) are expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In human disease, mitochondrial dysfunction, in the form of mtDNA mutations or disruption in overall mitochondrial biology, has been implicated in diabetes, Parkinson's disease, Alzheimer's disease, dementia, coronary artery disease, chronic fatigue syndrome, and ataxia ( 8 12 , 17 , 18 ). In broiler (meat-type) chickens, research has shown evidence of mitochondrial dysfunction related to susceptibility to ascites and to be influenced by orexin in broiler muscle ( 19 , 20 ). Mitochondria are also direct targets for some bacterial infections including Staphylococcus aureus , one of the most common causative agents in BCO ( 9 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human disease, mitochondrial dysfunction, in the form of mtDNA mutations or disruption in overall mitochondrial biology, has been implicated in diabetes, Parkinson's disease, Alzheimer's disease, dementia, coronary artery disease, chronic fatigue syndrome, and ataxia ( 8 12 , 17 , 18 ). In broiler (meat-type) chickens, research has shown evidence of mitochondrial dysfunction related to susceptibility to ascites and to be influenced by orexin in broiler muscle ( 19 , 20 ). Mitochondria are also direct targets for some bacterial infections including Staphylococcus aureus , one of the most common causative agents in BCO ( 9 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mRNA of prepro-orexin is expressed in the lateral hypothalamus area, known as a feeding center [ 4 , 9 ]. The orexin system is also expressed in peripheral tissues, including the kidney, adrenal gland, thyroid, testes, ovaries, jejunum, lung, pituitary gland, brown and white adipose tissues, and muscle [ 6 , 7 , 14 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Overview Of Orexinmentioning
confidence: 99%
“…The muscle was also investigated in the avian species as a main area of selection in modern broilers, leading to high metabolic demands within the muscle. To that end, the orexin system was shown to be expressed in the muscle and to regulate mitochondrial dynamics via fission- and fusion-related genes and their associated transcription factors [ 22 ]. In addition to the regulation of the orexin system within avian muscle, orexin treatment was also shown to impact mitochondrial biogenesis and functional genes, while also significantly decreasing the proton leak within a quail muscle cell line [ 22 ].…”
Section: Peripheral Role Of Orexinmentioning
confidence: 99%
See 1 more Smart Citation
“…Although orexin has been found in poultry for decades, its function is still inconclusive. Current evidence shows that orexin plays an important role in chicken for meat production, and would regulate the ATP level in mitochondria thereby increasing or decreasing feed intake [ 55 , 56 , 57 ].…”
Section: The Endocrine Regulation Of the Avian Appetitementioning
confidence: 99%